Peran Perdagangan Internasional dalam Mendorong Pembangunan Ekonomi dalam Mengentasan Kemiskinan di Indonesia - Khairani Alawiyah Matondang; Laura Magdalena Tambunan; Maria Audina Rumapea; Teresia Reginanta Ginting (Departement of Mathematics Education, 2024)
This research aims to determine the impact of international trade on Indonesia's economic growth. The type of research used is a literature review approach with a comprehensive search of academic databases, articles, journals and books. International trade plays an important role in driving Indonesia's economic growth through exports, product diversification and international partnerships. This study also highlights the challenges Indonesia faces in international trade, including fluctuations in currency exchange rates and the impact of global economic trends. This research concludes that international trade has an important role in forming the foundation of the Indonesian economy and positioning it as a major player in the global market. The study recommends that the government implement policies that support international trade, such as reducing tariff and non-tariff barriers, to increase the country's competitiveness in the global market. In addition, this study suggests that the government should focus on developing human resources and infrastructure to support industrial growth that can contribute to the country's economic development and poverty alleviation.